Dual Band Microstrip Bandpass Filter Using Coupling Structure for Wi-Fi Application - Sukri, Azmira Mohd; Din, Norashidah Md; Norzeli, Syamimi Mohd; Deros, Siti Noratiqah Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The Wi-Fi network connection is one of the largest network connection in world for a lot of telecommunication devices such as laptop and mobile phones. The design of a dual-band microstrip bandpass filter using coupling structure is proposed in this paper. The frequencies involved in for Wi-Fi application at frequencies of 2.4 and 5.8 GHz based on IEEE Regulation and Standard 802.11. The microstrip is used in filter design because of the low in cost and loss characteristics. The design of a microstrip bandpass filter that is created on coupling structure theory using end-coupled of quarter wavelength transmission line and parallel- coupled with a half-wavelenght resonators that operate at a dual-frequency band. Parametric analysis occur at open-stub condition, which involves the width, height and the gap to remove the harmonic frequency and obtain the good simulation results. Ansoft Designer Version 2.0 EM Simulator is used to design the filter. Simulations have been carried out to determine the filter’s S-Parameters performance. The design comply at dual frequency at half-wavelength with a bandwidth of 300MHz at both frequency as stated. The filter is then fabricated on a TMM4 substrate from Rogers, dielectric constant of 4.50, dissipation factor of 0.0020, substrate thickness of0.508 mm, copper thickness of 35 µm and the value of transmission line is 50Ω at both ports. The complete size of the filter is 55.4 × 3.52 mm2. The process of simulation and measurement is been done to observed the S- Parameter performance of the filter for the return loss and insertion loss.